Socio-economic Factors on the Evolution of Mortality in Europe in the XXI Century: Policy Proposals to Face the COVI D-19 Crisis - Blanco-Arana, María del Carmen (Universidad de Huelva, 2020)
In the midst of adverse effects from the COVID-19 pandemic, the global economy has been confronted with new challenges, among which is an increase in mortality as a consequence of the virus. The main objective of this article is to examine the socio-economic factors influencing the evolution of mortality in Europe in the 21st century, using a panel data for a fixed effects model. The findings suggest that the determinants most strongly connected to the evolution of mortality in Europe include: inequality, the number of beds available in hospitals and the unemployment rate. These results further highlight the importance of developing specific strategies to control these factors, and to assist developed economies in order to face potential economic and health crises, like the current pandemic, more effectively in the future.
Keywords: COVID-19 - Mortalidad - Europa; Socio-economic factors; COVID-19; Mortality; Panel Data; Europe